The story of mathematics from creating the pyramids to exploring infinity - Rooney, Anne
Long ago, the earliest human civilizations discovered the strange and fascinating quality of particular numbers and wove them into their superstitions and religions. Numbers have entranced people ever since. This book tells the story of mankind through mathematics from cave dwelling to modern life--